Transcriptional Silencing of MCL-1 Through Cyclin-Dependent Kinase Inhibition in Acute Myeloid Leukemia - Tibes, Raoul; Bogenberger, James M. (Frontiers in Oncology, 2019)
Acute myeloid leukemia (AML) is the most common adult acute leukemia. Survival remains poor, despite decades of scientific advances. Cytotoxic induction chemotherapy regimens are standard of care for most patients. Many investigations have highlighted the genomic heterogeneity of AML, and several new targeted therapeutic options have recently been approved. Additional novel therapies are showing promising clinical results and may rapidly transform the therapeutic landscape of AML. Despite the emerging clinical success of B-cell lymphoma (BCL)–2 targeting in AML and a large body of preclinical data supporting myeloid leukemia cell (MCL)–1 as an attractive therapeutic target for AML, MCL-1 targeting remains relatively unexplored, although novel MCL-1 inhibitors are under clinical investigation. Inhibitors of cyclin-dependent kinases (CDKs) involved in the regulation of transcription, CDK9 in particular, are being investigated in AML as a strategy to target MCL-1 indirectly. In this article, we review the basis for CDK inhibition in oncology with a focus on relevant preclinical mechanism-of-action studies of CDK9 inhibitors in the context of their therapeutic potential specifically in AML.